Topographic Contour Map of the Moon's South Pole Ridge - McCanaan, Kathryn; Animireddi, Venkata Satya Kumar; Barrett, Natasha; orcid:0000-0002-4964-1138; Boazman, Sarah; Gawronska, Aleksandra; Gilmour, Cosette; orcid:0000-0002-4978-530X; Halim, Samuel; Harish; Shah, Jahnavi; Kring, David A. (David Allen); et al. (Center for Lunar Science and Exploration, Lunar and Planetary Institute, 2019)
Lunar Reconnaissance Orbiter Lunar Orbiter Laser Altimeter (LOLA) 5-m elevation product over derived hillshade with solar azimuth 45° W and solar elevation 45°. High elevation: red and orange; Low elevation: purple and white.